Behind Closed Doors - Paris, B. A. (New York : St. Martins Griffin, 2017)
"Everyone knows a couple like Jack and Grace. He has looks and wealth; she has charm and elegance. Youd like to get to know Grace better. But its difficult, because you realize Jack and Grace are never apart. Some might call this true love. Others might ask why Grace never answers the phone. Or how she can never meet for coffee, even though she doesnt work. How she can cook such elaborate meals but remain so slim. And why there are bars on one of the bedroom windows.
"First published in Great Britain by MIRA/Harlequin, HarperCollins UK"--Title page verso.
Keywords: Spouses -- Fiction; Marital conflict -- Fiction; Abusive men -- Fiction; Family secrets -- Fiction; Spousal abuse -- Fiction; Abused women -- Fiction; Couples -- Fiction; Secrecy -- Fiction; Psychological fiction; Thrillers (Fiction)